Common law separation of spouses as a cause of physical separation and aivorce: specific traits - Cornejo Fava, María Teresa (2014)
This article addresses the constítutíonal príncíples of protecting families and promotíng marríage by the communíty and the State and theír recognítion as natural and fundamental institutíons of socíety, whíle díscussíng the contradiction of civil law with such constitutional princíples.